2001
DOI: 10.1074/jbc.m006252200
|View full text |Cite
|
Sign up to set email alerts
|

The Cytoplasmic C-terminal Fragment of Polycystin-1 Regulates a Ca2+-permeable Cation Channel

Abstract: The cytoplasmic C-terminal portion of the polycystin-1 polypeptide (PKD1(1-226)) regulates several important cell signaling pathways, and its deletion suffices to cause autosomal dominant polycystic kidney disease. However, a functional link between PKD1 and the ion transport processes required to drive renal cyst enlargement has remained elusive. We report here that expression at the Xenopus oocyte surface of a transmembrane fusion protein encoding the C-terminal portion of the PKD1 cytoplasmic tail, PKD1 (11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
90
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(96 citation statements)
references
References 44 publications
5
90
1
Order By: Relevance
“…In parallel, several efforts have been made to study the function of PC1 through investigation of a fusion protein that fused the PC1-C-terminal tail with the CD7 transmembrane or other transmembrane domains to locate it into the plasma membrane (28,(32)(33)(34)(35)(36). The overexpression of the plasma membrane-targeted C-terminal tail of PC1 stimulates GPCR to increase Ca 2ϩ release (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel, several efforts have been made to study the function of PC1 through investigation of a fusion protein that fused the PC1-C-terminal tail with the CD7 transmembrane or other transmembrane domains to locate it into the plasma membrane (28,(32)(33)(34)(35)(36). The overexpression of the plasma membrane-targeted C-terminal tail of PC1 stimulates GPCR to increase Ca 2ϩ release (32).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, significant amounts of polycystins have also been found in the endoplasmic reticulum (ER) (27)(28)(29)(30)(31). Although various studies have focused on the C-terminal tail of PC1 targeted to the plasma membrane and reported that it participates in several important signaling pathways (28,(32)(33)(34)(35)(36), the physiological significance of ER-localized PC1 has not been addressed in the literature.…”
mentioning
confidence: 97%
“…Anti-PC2 antibody (64) raised against a GST-PC2 fusion protein encoding the PC2 COOH-terminal cytoplasmic aa 687-968 was originally obtained from Dr. Oxana Beskrovnaya-Ibraghimova (Genzyme). Anti-CD16 monoclonal antibody (mAb) 3G8 was used as an Ig fraction as described (64,65). Anti-N-acetylated-␣-tubulin was obtained from Sigma, anti-calnexin from Stressgen, and anti-GM130 from BD Biosciences Pharmingen.…”
Section: Methodsmentioning
confidence: 99%
“…The PKD1 polypeptide gene product, polycystin-1 (PC1/TRPP1), is a 4,302-amino acid (aa) polypeptide with an NH 2 -terminal extracellular domain of ϳ3,000 aa, ϳ11 transmembrane domains, and a ϳ200-aa COOH-terminal cytoplasmic domain interacting with polycystin-2 (PC2/TRPP2) (46, 63), heterotrimeric G proteins, and the regulator of G protein signaling RGS7, among many other proteins. The COOH-terminal tail of PC1 also upregulates several transcriptional pathways, in part by regulated proteolysis (24), and activates endogenous Ca 2ϩ -permeable cation channels of 20 -30 pS in Xenopus laevis oocytes and HEK-293 cells (64,65). The PKD2 gene product, PC2, is a 968-aa polypeptide believed to function as a Ca 2ϩ -permeable cation channel in the endoplasmic reticulum and/or at the plasma membrane, independently or in complex with PC1 (11,26,33) or other proteins.…”
mentioning
confidence: 99%
“…At the present time, only the last 112 C-terminal residues of polycystin-1 have been convincingly shown to be involved in the regulation of a calcium channel, most probably through interaction with polycystin-2. This explains why mutations as far C-terminal as C4086X and others, 19,31,42 which result in removing the crucial polycystin-1 fragment that is implicated in regulating a cation channel, 12 result also in cyst formation and disease development.…”
Section: Novel Deletions In Hellenic Adpkd Families I Bouba Et Al 682mentioning
confidence: 99%